Water scarcity, livelihoods and food security : research and innovation for development - Harrington, Larry W.; Fisher, Myles (Earthscan studies in water resource management, 2014)
"This volume reviews the evolution of ten years' learning and discovery about water scarcity, livelihoods, and food security within the CGIAR Challenge Program on Water and Food. It draws on the experiences of over 100 projects conducted in ten river basins in the developing world. The book describes how the program's design evolved from an emphasis on water scarcity, water productivity, and water access to an emphasis on using water innovations to improve livelihoods and address development challenges in specific river basins. It shows how the research was used to foster change in stakeholder behavior, linking it to improved knowledge, attitudes, and skills, which were fostered by stakeholder participation, innovation, dialogue, and negotiation. The authors describe development challenges, their drivers and their political context, how to address them through technical, institutional, and policy innovations; and the consequences of change at different scales, time frames on equity, resilience, and ecosystem services. Overall, the work represents a major synthesis and landmark publication for all concerned with water resource management and sustainable development"--